2020
DOI: 10.1038/s41598-020-62872-5
|View full text |Cite
|
Sign up to set email alerts
|

The DsbA-L gene is associated with respiratory function of the elderly via its adiponectin multimeric or antioxidant properties

Abstract: Oxidative stress and inflammation play a key role in the age-related decline in the respiratory function. Adipokine in relation to the metabolic and inflammatory systems is attracting growing interest in the field of respiratory dysfunction. The present clinical and experimental studies investigated the role of the disulfide bond-forming oxidoreductase Alike protein (DsbA-L) gene, which has antioxidant and adiponectin multimeric (i.e. activation) properties, on the respiratory function of the elderly. We perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Its deficiency induces inflammation and it is upregulated under oxidative stress. 79 Thus, its increase can be the result of a defence mechanism against inflammation. Similar to GSTs, reduction in ALPI activity increases the risk of IBD as it can lead to altered intestine microbiome, inflammation, and changed permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Its deficiency induces inflammation and it is upregulated under oxidative stress. 79 Thus, its increase can be the result of a defence mechanism against inflammation. Similar to GSTs, reduction in ALPI activity increases the risk of IBD as it can lead to altered intestine microbiome, inflammation, and changed permeability.…”
Section: Discussionmentioning
confidence: 99%
“…DsbA-L exerts peroxidase activity and plays a crucial role in safeguarding cells against oxidative stress by facilitating the metabolism of exogenous substances, endogenous toxic metabolites, and free radicals [ 21 ]. Previous studies have shown that DsbA-L deficiency worsens oxidative stress and inflammation [ 22 , 23 ], while DsbA-L overexpression reduces ROS [ 24 ]. It is currently known that DsbA-L can protect PTCs by decreasing oxidative stress through improving mitochondrial function in DN [ 22 ], but the role of DsbA-L in peroxisome and the underlying mechanisms in DN remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Ero1-α induces calcium transfer from the ER to the mitochondria and leads to excessive generation of mtROS by inducing IP3R1 oxidation and ERp44 from IP3R1 ( 66 ). DsbA-L, a multifunctional protein, localized in the mitochondrial matrix, ER and MAMs fraction, is also involved in the production of mtROS ( 67 ). The inductive modulation of p66Shc on mtROS production and mitochondrial fission is attributed to Ser36 phosphorylation.…”
Section: The Cellular Processes Mediated By Mams In Cardiac Hypertrophymentioning
confidence: 99%